Marine-derived chromopeptide A, a novel class I HDAC inhibitor, suppresses human prostate cancer cell proliferation and migration - SUN Jing-ya; WANG Ji-dong; WANG Xin; LIU Hong-chun; ZHANG Min-min; LIU Yu-Chih; ZHANG Chen-hua; SU Yi; SHEN Yan-yan; GUO Yue-wei; SHEN Ai-jun; GENG Mei-yu (Acta Pharmacologica Sinica; Vol 38, No 4 (April 2017): Acta Pharmacologica Sinica, 2017)
Histone deacetylases (HDACs), especially HDAC1, 2, 3 and 4, are abundantly expressed and over-activated in prostate cancer that is correlated with the poor prognosis. Thus, inhibition of HDAC activity has emerged as a potential alternative option for prostate cancer therapy. Chromopeptide A is a depsipeptide isolated from the marine sediment-derived bacterium Chromobacterium sp. HS-13-94; it has a chemical structure highly similar to FK228, a class I HDAC inhibitor that is approved by FDA for treating T-cell lymphoma. In this study, we determined whether chromopeptide A, like FK228, acted as a class I HDAC inhibitor, and whether chromopeptide A could inhibit the growth and migration of human prostate cancer in vitro and in vivo. HDAC enzyme selectivity and kinetic analysis revealed that chromopeptide A selectively inhibited the enzymatic activities of HDAC1, 2, 3 and 8 in a substrate non-competitive manner with comparable IC50 values for each HDAC member as FK228 in vitro. Importantly, chromopeptide A dose-dependently suppressed the proliferation of human prostate cancer cell lines PC3, DU145 and LNCaP with IC50 values of 2.43±0.02, 2.08±0.16, and 1.75±0.06 nmol/L, respectively, accompanied by dose-dependent inhibition of HDAC enzymatic activity in PC3 and DU145 cells. Chromopeptide A (0.2–50 nmol/L) caused G2/M phase arrest and induced apoptosis in the prostate cancer cell lines. Moreover, chromopeptide A dose-dependently inhibited the migration of PC3 cells. In mice bearing PC3 prostate cancer xenografts, intravenous injection of chromopeptide A (1.6, 3.2 mg/kg, once a week for 18 d) significantly suppressed the tumor growth, which was associated with increased expression levels of Ac-H3 and p21 in tumor tissues. Our results identify chromopeptide A as a novel class I HDAC inhibitor and provide therapeutic strategies that may be implemented in prostate cancer.